Tailoring aggregation of silver nanoparticles via crystal violet: A surface-enhanced Raman scattering perspective - de Oliveira, Tatiana Aparecida [UNESP]; Setti, Grazielle O. [UNESP]; Rubira, Rafael Jesus Gonçalves [UNESP]; Constantino, Carlos J.L. [UNESP] (Elsevier, 2025)
Surface-enhanced Raman Scattering (SERS) enables the detection of target molecules at low concentrations. In this study, SERS spectra of crystal violet (CV) were obtained using colloidal silver nanoparticles (AgNPs) to systematically evaluate how CV concentration modulates AgNPs aggregation and, consequently, the SERS response. By combining SERS data with UV–Vis, dynamic light scattering (DLS), zeta potential, and scanning electron microscopy (SEM), we show that intermediate CV concentration induces maximum aggregation and hotspot formation, resulting in the most intense SERS signal. The SERS spectra of CV exhibited an atypical behavior, revealing a how CV concentration influences AgNPs aggregation. At low concentrations (1.8 ×10−9 mol/L), a weak SERS signal was observed, with minimal changes in AgNPs size (100 nm) and zeta potential (-30 mV), suggesting limited aggregation. At 3.6 × 10−7 mol/L, the most intense SERS signal coincided with maximum aggregation (500 nm, +3 mV). However, at higher concentrations (9.1 ×10−7 mol/L), the SERS signal decreased significantly, indicating possible colloidal degradation (precipitation due to excessive aggregation). Size measurements at 9.1 × 10−7 mol/L (+14 mV) and 1.8 × 10−5 mol/L (+28 mV) suggest reduced aggregation. Our current hypothesis is as follows: at low CV concentrations, despite the positive charge of the CV, the negative zeta potential of the AgNPs is largely maintained, preventing significant aggregation due to electrostatic repulsion. At intermediate concentrations, partial coating of AgNPs by CV neutralizes their surface charge, bringing the zeta potential closer to zero and facilitating aggregation. At high concentrations, a full CV coating on the AgNPs increases the zeta potential to positive values, reinstating electrostatic repulsion and preventing further aggregation.